Differential tractography pipelines study in asymptomatic individuals with cerebral small vessel disease - Safri, Amanina Ahmad (2022)
Introduction: Cerebral small vessel disease (CSVD) is frequently discovered as an asymptomatic (‘silent’) finding during magnetic resonance imaging (MRI) brain scanning. Diffusion-based MRI, such as diffusion tensor imaging (DTI), is an emerging neuroimaging technique to detect and evaluate the CSVD manifestations, such as white matter hyperintensities (WMHs). DTI has been used progressively, but there is no gold standard for optimising the DTI pipeline processing, especially in the CSVD study. Therefore, to make the best use of DTI, several technical and methodological considerations must be made. Objective: The goal of this study is to establish a series of DTI pipeline processing either in a single or a combination of multiple well-established software packages in order to study their compatibility, reproducibility, and reliability in the assessment of white matter ischaemic integrity in asymptomatic CSVD. Methods: Sixty (n = 60) asymptomatic people (mean age, 39.82 years old ± 11.32) were recruited and had their brains scanned with a 3T MRI scanner. Twenty (n = 20) of the participants had WMHs. Four pipeline processing were established: P1(MedINRIA), P2 (DSI Studio), P3 (DTI Toolkit and TrackVis), and P4 (3Dslicer). Results: Each established DTI pipeline processing profile and user interface differences were discussed, including the programming language used, estimated total processing times, and their strengths and weaknesses. The comparison between each of the DTI pipelines processing was determined to be P2 as the best among the other pipelines processing used in this study based on the highest relative score of user interface differences. P2 also has a good reliability score (α = 0.86). Conclusion: This study established the compatibility, reproducibility, and reliability of established DTI pipelines in the assessment of white matter ischemic integrity in apparently asymptomatic CSVD. It provides a comprehensive analysis that can improve and standardise the identification of WMHs and allow for a more robust white matter integrity assessment. Our findings show that the acceptable reliability score in the established DTI pipelined processing is P2 (DSI Studio), which can serve as an ideal pipeline processing to assess white matter tractography in CSVD.